Prescribed stimulant medications: Trends in the last decade, pre and post COVID-19 response - Meelee L. Kim; Netrali Dalvi; Danielle DeNufrio Valerio; Gail K. Strickler; Leonard D. Young (Elsevier, 2023)
Background: Recent studies indicate that COVID-19 has had a significant impact on access and continuity to opioid and benzodiazepine medications; little is known about its effect on access to and utilization of stimulant medications. Objective: To investigate trends of dispensed stimulant medications in relation to the COVID-19 pandemic response. Methods: Stimulant prescriptions dispensed during 2011-2021 were analyzed using the Massachusetts Prescription Drug Monitoring Program (PDMP), the state's data repository for all controlled substance medications dispensed to residents from retail pharmacies and out of state mail-order pharmacies. Statewide trends were estimated by age group, sex, and stimulant-naïve patients (individuals with no stimulant prescription in the prior one-year period). Results: Overall, stimulant prescriptions increased 70% from 2011 to 2021. Wide differences by sex and age groups were found pre and post COVID response periods. Between 2019 and 2021, stimulant prescriptions for males 12-18 years old decreased 14.6% compared to 0.9% for females. Female stimulant-naïve patients ages 25-34 increased more than males between 2019 and 2021 (11.6% compared to <1%, respectively) and females ages 35-44 increased 4.1% while males decreased by 2.7%. Conclusions: Administrators, clinicians, and policy makers should closely monitor stimulant prescribing trends, a critical step in improving access to and quality of care.